PERANAN LEMBAGA PERBANKAN DALAM PEMBANGUNAN EKONOMI NASIONAL - Ridduwan, Muhammad (Solusi, 2024)
Banking institution are institution that play an important role in the economic development of acountry. Likewise with indonesia. From a historical perspective the growth of national bankinginstitution has actually existed since the dutch colonial period which has carried out bankingfunction, namely the cash and fund collection function, the credit granting function, the functionof printing and distributing money, as well as the supervisory function. This function and dutieswere then continued in the modern banking era.